2017
DOI: 10.18632/oncotarget.21505
|View full text |Cite
|
Sign up to set email alerts
|

JNK inhibitor alleviates apoptosis of fetal neural stem cells induced by emulsified isoflurane

Abstract: Isoflurane can provide both neuroprotection and neurotoxicity in various culture models and in rodent developing brains. Emulsified Isoflurane (EI) is an emulsion formulation of isoflurane, while its underlying molecular mechanism of developemental nerve toxicity largely remains unclear. We hypothesized that EI induced fetal neural stem cells (FNSCs) apoptosis, endoplasmic reticulum (ER) stress and c-Jun N-terminal kinase (JNK) activation.FNSCs were isolated from the cortex of SD rats during 14 days of gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
3
0
2
Order By: Relevance
“…c-Jun N-terminal kinases (JNKs) belong to the mitogen-activated protein kinase family (MAPK) and are involved in apoptosis. The study found that JNKs and their downstream c-Jun were involved in the neurotoxicity of sevoflurane in the neonatal brain; meanwhile, up-regulation of HIPK2, JNK, and c-Jun was observed in hippocampal neurons of mice exposed to sevoflurane, continued until adulthood ( 14 ), inhibition of JNK found that mice can restore normal neurodevelopment and cognitive function ( 14 , 15 ), but activation of this signaling pathway can induce neuronal apoptosis ( 16 ), which may be linked to its upregulation of Connexin-43, and its increase can lead to cognitive dysfunction ( 17 ). And when JNK antagonists were given to these newborn mice, it was found that the expression of HIPK2 was not affected ( 14 ), so JNKs/c-Jun signaling pathway may be directly induced by general anesthetics, but not related to the presence of HIPK2.…”
Section: Related Signaling Pathwaysmentioning
confidence: 99%
“…c-Jun N-terminal kinases (JNKs) belong to the mitogen-activated protein kinase family (MAPK) and are involved in apoptosis. The study found that JNKs and their downstream c-Jun were involved in the neurotoxicity of sevoflurane in the neonatal brain; meanwhile, up-regulation of HIPK2, JNK, and c-Jun was observed in hippocampal neurons of mice exposed to sevoflurane, continued until adulthood ( 14 ), inhibition of JNK found that mice can restore normal neurodevelopment and cognitive function ( 14 , 15 ), but activation of this signaling pathway can induce neuronal apoptosis ( 16 ), which may be linked to its upregulation of Connexin-43, and its increase can lead to cognitive dysfunction ( 17 ). And when JNK antagonists were given to these newborn mice, it was found that the expression of HIPK2 was not affected ( 14 ), so JNKs/c-Jun signaling pathway may be directly induced by general anesthetics, but not related to the presence of HIPK2.…”
Section: Related Signaling Pathwaysmentioning
confidence: 99%
“…These changes may have detrimental effects on cognition after isoflurane anesthesia, 22,65 the magnitude of which is clearly age‐dependent 66 . The JNK inhibitor alleviates emulsified isoflurane‐induced apoptosis of fetal NSCs 67 . l ‐Theanine and simvastatin attenuate isoflurane‐induced neurogenetic damage and neurocognitive deficits in developing rats' brains through upregulation of the Akt/GSK‐3β signaling pathway 68,69 …”
Section: Effects Of Anesthetic Drugs On Nscs and Their Mechanismsmentioning
confidence: 99%
“… 66 The JNK inhibitor alleviates emulsified isoflurane‐induced apoptosis of fetal NSCs. 67 l ‐Theanine and simvastatin attenuate isoflurane‐induced neurogenetic damage and neurocognitive deficits in developing rats' brains through upregulation of the Akt/GSK‐3β signaling pathway. 68 , 69 …”
Section: Effects Of Anesthetic Drugs On Nscs and Their Mechanismsmentioning
confidence: 99%
“…При ýтом ключевая роль в предупреждении им развития нарушений деятельности ЦНС и их компенсации, очевидно, принадлежит сохранению способности нервной ткани к репарации, связанной с обеспечением адекватного функционирования резидентных нейральных СК головного мозга [5,6]. В основе реализации данного механизма лежит, по-видимому, не только прямое стимулирующее влияние блокады JNK-опосредованного сигналинга в отношении прогрессии клеточного цикла родоначальных ýлементов, но и требующее дальнейшего ýкспериментального подтверждения -торможение процессов их JNK-зависимого апоптоза [13][14][15].…”
Section: заключениеunclassified